Peningkatan Efisiensi Administrasi Melalui Sistem Kearsipan Digital di Pesantren Al-Amalul Khair Palembang - Yesita Astarina; Dwi Riana; Sunanto Sunanto; Tika Handayani; Faridatuljana Binti Mohd Noor (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Islamic boarding schools often face administrative inefficiencies due to the use of manual archiving systems, leading to difficulties in document retrieval and high risks of data loss. This community service program aims to improve efficiency by implementing a Microsoft Access-based digital archiving system at Al-Amalul Khair Islamic Boarding School in Palembang. The method applied is Participatory Action Research, which includes needs analysis, system design, hands-on training, and evaluation. The results show a significant increase in efficiency, with document retrieval time reduced from 30 minutes to under 2 minutes. The digital capacity of administrative staff has also increased, as demonstrated by the enhanced knowledge and skills of the administrative staff, who are now able to operate the Microsoft Access-based digital archiving application. This program has successfully created an applicable system, complete with a user guide and copyright protection. Therefore, the implementation of the digital archiving system has proven to be a strategic solution in strengthening the administrative governance of the pesantren in the modern era.